Increased risk of erectile dysfunction among males with central serous chorioretinopathy – a retrospective cohort study. (23rd September 2012) - Tsai, Der‐Chong; Huang, Chin‐Chou; Chen, Shih‐Jen; Chou, Pesus; Chung, Chia‐Min; Chan, Wan‐Leong; Huang, Po‐Hsun; Lin, Shing‐Jong; Chen, Jaw‐Wen; Leu, Hsin‐Bang
Abstract. Purpose: Central serous chorioretinopathy (CSCR) mostly affects middle‐aged men and has been associated with stress and hypercortisolism. We hypothesized that some factors prone to inducing CSCR could also have a harmful effect on erectile function. This study aimed to investigate the risk of subsequent erectile dysfunction after CSCR using Taiwan National Health Insurance Research Database. Methods: The study cohort (n = 1220) consisted of newly diagnosed CSCR men aged 19–64 years between 1999 and 2007, and men matched for age, monthly income and time of enrolment were randomly selected as the control group (n = 10870). Cox proportional hazard regressions were performed to calculate the hazard ratios (HR) of clinically diagnosed erectile dysfunction (including organic origin and/or psychogenic origin) for the two groups. Erectile dysfunction‐free survival analysis was assessed using a Kaplan–Meier method. Results: Twenty‐five patients (2.0%) from the CSCR cohort and 103 (0.9%) from the control group were diagnosed erectile dysfunction clinically during a mean observation period of 4.3 years. Patients with CSCR had a significantly higher incidence of erectile dysfunction diagnosis than those without CSCR (p < 0.001). After adjusting for age, geographic location, chronic comorbidities and medication habits, patients with CSCR were found to have a 2.22‐fold [95% confidence interval (CI), 1.42–3.46] higher hazard ratio of a subsequent erectile dysfunction diagnosis than the matched controls. The adjusted HR for organic and psychogenic erectile dysfunction were 2.14 (95% CI: 1.34–3.44) and 3.83 (95% CI: 1.47–10.01), respectively. Conclusions: Central serous chorioretinopathy was independently associated with an increased risk of being diagnosed with erectile dysfunction.